2014
DOI: 10.29244/cb.1.2.58-65
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Analysis, α-glucosidase Inhibition Activity <i>in-vitro</i> and Enzyme Kinetics of Ethyl Acetate and Hexane Extracts of <i>Graptophylum pictum</i> (L.) Griff

Abstract: The species Graptophylum pictum (L.) Griff, also known as “daun ungu” in Indonesia, is a traditional herbaceous plant believed to have antidiabetic potential. The number of people in the world with diabetes has increased dramatically over the recent years. The treatment of type II diabetes is complicated by several factors inherent to the disease. Elevated postprandial hyperglycemia is one of the risk factors and the intestinal digestive enzyme α-glucosidase plays a vital role in carbohydrate metabolism. One o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…After incubation at 37°C for 5 min, 50 μl of p -NPG was added as substrate, and the reaction proceeded at 37°C for 30 min. Kinetic parameters were determined using Michaelis–Menten kinetics [ 31 , 32 ].…”
Section: Methodsmentioning
confidence: 99%
“…After incubation at 37°C for 5 min, 50 μl of p -NPG was added as substrate, and the reaction proceeded at 37°C for 30 min. Kinetic parameters were determined using Michaelis–Menten kinetics [ 31 , 32 ].…”
Section: Methodsmentioning
confidence: 99%
“…Graptophyllum pictum is endemic to Papua New Guinea, although it has now spread to several other countries, including Asia (such as Indonesia), Ghana, India, Mexico, and Bolivia (Makkiyah et al, 2021). Several studies reported that this plant leaves contained phytochemicals including glycosides, flavonoids, alkaloids, steroids, phenolic, carbohydrates, phenolics, anthraquinones, coumarins, and tannins (Jiangseubchatveera et al, 2017;Poh-Yen et al, 2018). The plant's leaves are beneficial in traditional medicine for treating rheumatism, hemorrhoid, scabies, swelling, hepatomegaly, constipation, ulcers, urinary infection, maturing boil process, and ear disease and smoothing skin, increasing fertility, and wound healing (Ibrahim et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The plant's leaves are beneficial in traditional medicine for treating rheumatism, hemorrhoid, scabies, swelling, hepatomegaly, constipation, ulcers, urinary infection, maturing boil process, and ear disease and smoothing skin, increasing fertility, and wound healing (Ibrahim et al, 2022). Furthermore, the plant leaves exhibit multiple pharmacological properties, including anticancer, antibacterial, antioxidant (Jiangseubchatveera et al, 2015), antihemorrhoid (Kusumawati et al, 2022), nephroprotective (Srinivasan et al, 2015), inhibitory a-glucosidase (Nurcholis et al, 2014), and photoprotective activities (Poh-Yen et al, 2018). However, standardization of the G. pictum extract is still necessary to demonstrate the phytochemical content and pharmacological activity.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations